QbD approach to HPLC method development and validation of ceftriaxone sodium - Krunal Y. Patel; Zarna R. Dedania; Ronak R. Dedania; Unnati Patel (SpringerOpen, 2021)
Abstract Background Quality by design (QbD) refers to the achievement of certain predictable quality with desired and predetermined specifications. A quality-by-design approach to method development can potentially lead to a more robust/rugged method due to emphasis on risk assessment and management than traditional or conventional approach. An important component of the QbD is the understanding of dependent variables, various factors, and their interaction effects by a desired set of experiments on the responses to be analyzed. The present study describes the risk based HPLC method development and validation of ceftriaxone sodium in pharmaceutical dosage form. Results An efficient experimental design based on central composite design of two key components of the RP-HPLC method (mobile phase and pH) is presented. The chromatographic conditions were optimized with the Design Expert software 11.0 version, i.e., Phenomenex ODS column C18 (250 mm × 4.6 mm, 5.0 μ), mobile phase used acetonitrile to water (0.01% triethylamine with pH 6.5) (70:30, v/v), and the flow rate was 1 ml/min with retention time 4.15 min. The developed method was found to be linear with r2 = 0.991 for range of 10-200 μg/ml at 270 nm detection wavelength. The system suitability test parameters, tailing factor and theoretical plates, were found to be 1.49 and 5236. The % RSD for intraday and inter day precision was found to be 0.70-0.94 and 0.55-0.95 respectively. The robustness values were less than 2%. The assay was found to be 99.73 ± 0.61%. The results of chromatographic peak purity indicate the absence of any coeluting peaks with the ceftriaxone sodium peak. The method validation parameters were in the prescribed limit as per ICH guidelines. Conclusion The central composite design experimental design describes the interrelationships of mobile phase and pH at three different level and responses to be observed were retention time, theoretical plates, and peak asymmetry with the help of the Design Expert 11.0 version. Here, a better understanding of the factors that influence chromatographic separation with greater confidence in the ability of the developed HPLC method to meet their intended purposes is done. The QbD approach to analytical method development was used for better understanding of method variables with different levels.